Penerapan Algoritma C4.5 Dalam Sistem Prediksi Kelulusan Santri Tahfidz Qur’an - Siregar, Putri Aprilia; Putri, Raissa Amanda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Tahfidz Ulumul Qur'an Islamic Boarding School Medan is an Islamic religious educational institution that focuses on educating memorizers of the Al-Qur'an. However, not all students can graduate on time according to the study period taken, resulting in a buildup of students who graduate not on time. The determination of student graduation is based on several criteria that students must pass while studying at the Tahfizd Ulumul Qur'an Islamic Boarding School. Therefore, the C4.5 algorithm is a machine learning method used to build a decision tree based on 160 students' data. The data used in this research includes various factors that influence students' graduation, such as Makhorijul Letters, Memorizing, Discipline, and Relevant lafadz. The results of this research show that the C4.5 algorithm is able to provide accurate predictions regarding the graduation of Tahfidz Qur'an students with an accuracy rate of 98.21%. Where, based on the results of processing student data, it was found that 107 data of students graduated on time and 53 did not graduate on time.